Probabilistic Assessment of Civil Infrastructure Resilience to Earthquakes. (10th September 2014) - Franchin, Paolo; Cavalieri, Francesco; Iervolino, Iunio; Ellingwood, Bruce R.
Abstract The large losses occurred in the past due to earthquakes, even in highly developed countries, as well as the ensuing prolonged inactivity of the stricken societies, imparted momentum to research into regional seismic impact and community resilience to earthquakes. Need for comprehensive and consistent modeling is apparent, and this work presents a contribution in this direction. The extension of a recently developed civil infrastructure simulation framework to the evaluation of resilience, as well as the introduction of a new infrastructure network‐based resilience metric represent the novelties of the article and allow one to explore the effect that sources of uncertainty and key vulnerability factors have on the probability distribution of resilience.